ITS2 Nucleotide Sequence Analysis and Cleaned Culture Production of Butea monosperma var. lutea - Kanjanawattanawong, Supanath; Singbumrung, Natthathida; Rianthong, Thitinun; Wamaedeesat, Raheema (Princess of Naradhiwas University Journal, 2019)
Yellow Flame of the Forest (Butea monosperma (Lam.) Kuntze var. lutea (Witt.) Maheswari) is a rare ornamental and medicinal plant used for the treatment of vaginal discharge, skin diseases, and as an antidiarrheal. Thus, the discrimination between yellow and orange varieties is important, so DNA barcoding technique using specific primers for matK, ITS2 and rbcL regions were performed. As a result, it was found that only ITS2 region could be amplified (66.67%). The BlanstN DNA analysis also showed that ITS sequences had high homology (99%) to B. monosperma (AC: KJ436383). However, the multiple sequence alignment of these amplified fragments showed no difference between the yellow and orange varieties. Thus, additional markers should be developed for more effective discrimination. Of these, the ITS2 sequences have already been deposited in the NCBI database (AC: MK651821, MK651822, MK651823, and MK651824). Because the plant has a high risk of extinction, micropropagation is an effective method to increase its quantity and maintain these rare species. However, the surface of this plant is covered with dense hairs, which makes surface sterilization difficult. Therefore, surface sterilization techniques, with the addition of several disinfectants, into various culture media, were investigated. The lowest contamination (30.0%) with 72.4% of survivability was achieved by adding 400 µl/l Plant Preservatives Mixture (PPM) in MS media. The use of 400 µl/l PPM, in combination with BA 2 or 4 mg/l to stimulate growth of lateral bud, showed a lower survival percentage than the control treatment (25-58.3%). For the addition of various microbial disinfectant agents in liquid WPM (Woody Plant Media), the lowest contamination (22.2%) was obtained from liquid WPM containing 400 µl/l PPM in combination with 250 mg/l streptomycin or 250 mg/l carbendazim. The highest surviving rate (90.8%) was observed in the media supplement with PPM and streptomy